Regulation of HSV-1 Immediate Early Gene Expression - Hupel, Thomas (My University, 1990)
Herpes simplex Virus Type 1 expresses three different classes of genes, immediate early, early, and late, during a lytic infection. Immediate early genes are the first class of genes expressed and they are the only genes expressed independently of de novo viral protein synthesis. This unique characteristic is thought to be the result of the activation of immediate early genes by Vmw65, a protein brought into the cell as a component of the infecting virion. Vmw65 transactivates through the target sequence TAATGARAT (R= purine) which is present at least once in all immediate early transcription regulatory regions. By inserting minimal synthetic promoters, containing the TAATGARAT sequence, into the thymidine kinase locus of the herpes simplex virus type 1 genome I determined that transactivation by Vmw65 is not sufficient to confer on the linked sequences the complete immediate early pattern of gene expression. Furthermore through a transient expression assay I determined that the TAATGARAT sequence element, by itself, when linked to a TATA box is sufficient to act as a target for Vmw65 transactivation.
Keywords: herpes; herpes simplex virus; gene; expression; regulate